Smallholder Pig Value Chains Development (SPVCD) and Safe Food Fair Food (SFFF) Project - Household level and pig bio data - Pezo, Danilo; Grace, Delia; Dione, Michel; Roesel, Kristina; Kungu, Joseph; Erume, Joseph; Akol, Joyce; Musewa, Angella (2024)
SPVCD aims to increase the productivity of small-scale pig systems in sustainable ways, making meat more available and affordable to poor consumers across Uganda & SFFF is working to improve the livelihoods of the poor by reducing the health risks associated with pig-sourced food and by improving nutrition and market access for smallholders., SPVCD aims to increase the productivity of small-scale pig systems in sustainable ways, making meat more available and affordable to poor consumers across Uganda & SFFF is working to improve the livelihoods of the poor by reducing the health risks associated with pig-sourced food and by improving nutrition and market access for smallholders. This dataset is from the household-level survey, together with the pigs surveyed in the same households.